Bridging Knowledge and Character: Cultivating Student Development through Islamic Educational Leadership - Rekan, Abd. Aziz; Howell, Hafeezur-Rahman; Mohamad Salleh, Muhamad Nasir; Kassim, Noorafini; Rokhimawan, M. Agung (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Higher Education Institutions (HEIs) play a pivotal role in advancing comprehensive and balanced human capital development. Amid rapid globalization, digital transformation, and the erosion of moral values, HEIs face increasing challenges in cultivating well-rounded individuals who can meet contemporary demands while upholding ethical and spiritual principles. As market-driven education increasingly prioritizes technical and professional competencies, the nurturing of moral integrity and holistic growth is often neglected. Therefore, this study investigates how the Arabic Language Education Program contributes to holistic human capital development through Islamic educational leadership, focusing on students’ lived experiences, leadership formation, and value-based educational practices. Employing a mixed-methods approach with an exploratory sequential design, the research commenced with qualitative data collection through interviews with 50 informants and document analysis, followed by a quantitative survey involving 184 respondents. Data were analyzed thematically and descriptively, and findings from both phases were triangulated to enhance interpretive validity. The study identifies four principal dimensions of human capital development: (i) Leadership Experiences and Opportunities, (ii) Religious Development and Spiritual Strengthening, (iii) Local and Socio-Cultural Influences, and (iv) Challenges and Obstacles in Human Capital Development. The findings provide critical insights for policymakers and stakeholders in refining leadership policies and educational strategies, thereby reinforcing the foundations of human development agendas at both national and global levels.